Menghidupkan Potensi Desa: Ecoprint Taplak Meja Bersama Ibu-Ibu Desa Karya Mukti - Asmarita Asmarita; Choirunnisa Choirunnisa; Merita Auli; Yunizir Djakfar (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2025)
This community service activity aims to develop creativity and empower women in Karya Mukti Village as an effort to revive the village's potential through ecoprint tablecloth training. Ecoprint is a fabric dyeing technique that uses natural materials such as leaves and flowers, which is not only environmentally friendly but also capable of producing high artistic value products. Through this training, it is expected that participants can improve their skills, creativity, environmental awareness, and the local economic potential of the community. The methods used in this community service include socialization, demonstration, direct practice, and result evaluation. The training results show that the participating women were able to produce ecoprint products with unique motifs in the form of tablecloths, which have high aesthetic value and the potential to serve as an effort to empower the community’s economy.